2009
DOI: 10.1038/cdd.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Role of FK506-binding protein 51 in the control of apoptosis of irradiated melanoma cells

Abstract: FK506-binding protein 51 (FKBP51) is an immunophilin with isomerase activity, which performs important biological functions in the cell. It has recently been involved in the apoptosis resistance of malignant melanoma. The aim of this study was to investigate the possible role of FKBP51 in the control of response to ionizing radiation (Rx) in malignant melanoma. FKBP51-silenced cells showed reduced clonogenic potential after irradiation compared with non-silenced cells. After Rx, we observed apoptosis in FKBP51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
160
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 35 publications
6
160
0
Order By: Relevance
“…Notably, inhibition of the autophagy signaling pathway by 3-MA significantly enhanced OX-induced cell apoptosis in vitro and tumor suppression in vivo, indicating that the activation of autophagy by OX may reduce OX cytotoxicity. The results of the current study are consistent with previous findings (17,18) and a recent report (14), in which cisplatin-induced autophagy reduced its apoptotic effect by downregulating the ER stress-mediated apoptosis pathway and the mitochondrial apoptosis pathway in HeLa cells. Considering the results of the present study, it is plausible that OX-activated autophagy may be responsible for the observed clinical inefficiency of OX in specific patients with colon cancer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, inhibition of the autophagy signaling pathway by 3-MA significantly enhanced OX-induced cell apoptosis in vitro and tumor suppression in vivo, indicating that the activation of autophagy by OX may reduce OX cytotoxicity. The results of the current study are consistent with previous findings (17,18) and a recent report (14), in which cisplatin-induced autophagy reduced its apoptotic effect by downregulating the ER stress-mediated apoptosis pathway and the mitochondrial apoptosis pathway in HeLa cells. Considering the results of the present study, it is plausible that OX-activated autophagy may be responsible for the observed clinical inefficiency of OX in specific patients with colon cancer.…”
Section: Discussionsupporting
confidence: 83%
“…It has previously been reported that the activation of autophagy in cancer cells inhibits therapy-induced apoptosis (17,18). In the current study, OX was observed to induce apoptosis as well as autophagy in CT26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] On the other hand, some cancer cells can utilize activated autophagy to ameliorate deficiencies in nutrition and oxygen, caused by rapid fission and ischemia. [10][11][12] BECN1/Beclin1, an ortholog of Vps30/Atg6 in yeast, is a central component in autophagy and also plays crucial roles in development, tumorigenesis and neurodegeneration. 7 Interestingly, BECN1 was initially discovered not as an autophagy protein but rather as an interaction partner for the antiapoptotic protein BCL2.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we provided evidence that targeting of FK506 binding protein 51 (FKBP51) with siRNA determined a significant apoptosis sensitizing effect of irradiated melanoma [5]. Our studies have highlighted a relevant role for FKBP51 in melanoma resistance to genotoxic agents [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have highlighted a relevant role for FKBP51 in melanoma resistance to genotoxic agents [5][6][7]. To find out molecular targets for radiosensitizing strategies of melanoma, we investigated the changes of protein profiles in irradiated melanoma depleted or not of FKBP51, by protein microarray approach.…”
Section: Introductionmentioning
confidence: 99%